2019
DOI: 10.1158/1078-0432.ccr-18-2581
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocity between Radiotherapy and Cancer Immunotherapy

Abstract: The clinical success of immune checkpoint inhibitors in treating metastatic and refractory cancers has generated significant interest in investigating their role in treating locally advanced diseases, thus requiring them to be combined with standard treatments in the hope of producing synergistic antitumor responses. Radiotherapy, in particular, has long been hypothesized to have actions complementary to those of immune checkpoint blockade, and a growing body of evidence indicates that cancer immunotherapy may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 79 publications
1
92
0
Order By: Relevance
“…This phase II trial of ipilimumab with stereotactic radiotherapy describes satisfactory outcomes and low toxicities, lending support to the further investigation of combined-modality therapy for metastatic cancers. [162]. Hence, the combination of radiotherapy and immunotherapy is a promising modality for cancer treatment and is already supported by a well-designed clinical trial [163].…”
Section: Ferroptosis/ Necroptosismentioning
confidence: 98%
“…This phase II trial of ipilimumab with stereotactic radiotherapy describes satisfactory outcomes and low toxicities, lending support to the further investigation of combined-modality therapy for metastatic cancers. [162]. Hence, the combination of radiotherapy and immunotherapy is a promising modality for cancer treatment and is already supported by a well-designed clinical trial [163].…”
Section: Ferroptosis/ Necroptosismentioning
confidence: 98%
“…Moreover, radiation activates antitumor immune responses by triggering the stimulator of interferon genes (STING)-mediated DNAsensing pathway, increasing infiltration of CD8+ T cells while reducing myeloid-derived suppressor cell accumulation, and upregulating the surface expression of PD-L1 on tumor cells. 29 On the other hand, immunotherapy may also sensitize tumors to radiation by promoting tumor blood vessel normalization, improving tissue perfusion, and decreasing intratumoral hypoxia. 30,31 It has been shown that the combination of immunotherapy and radiotherapy is well tolerated by most patients with solid cancers.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The accumulation of mutant nucleic acid and proteins increases the odds of ICB treatment triggering tumor immunogenicity [ 84 , 85 ]. Besides modulating the release of antigens, the MHC molecules on tumor cells are also upregulated upon radiation, which activates the killing of T cells against tumors by binding to T cell receptors (TCRs) in the form of MHC-peptide transmitted by antigens presentation [ 86 , 87 ]. Furthermore, the irradiated tumor cells can also release DAMP and cytokines, which can enhance the translocation capacity of immune cells.…”
Section: Potential Mechanism Of Radiation-induced Abscopal Effectsmentioning
confidence: 99%
“…Radiation damage triggers the release of nuclear DNA into the cytosol, and cGAS can identify the mutant DNA in the cytoplasm and catalyzes the production of cGAMP, which serves as a second messenger to activate the ER membrane adaptor protein STING, which further stimulates TBK1 to activate the downstream transcription factors IRF3 and NF-κB. Subsequently, the expression of downstream type I interferon (IFN-I) is upregulated by the activated cGAS-STING axis through IRF3/NF-κB-dependent transcriptional activation ( Figure 2 ) [ 87 , 90 , 91 ].…”
Section: Potential Mechanism Of Radiation-induced Abscopal Effectsmentioning
confidence: 99%